1996
DOI: 10.1093/rheumatology/35.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Diagnosis in Acute and Subacute Oligoarthritis of Unknown Origin

Abstract: A total of 146 consecutive patients between 18 and 60 yr of age with oligoarthritis of unknown origin (< or = 6 active joints, < or = 8 weeks duration) were examined by a variety of clinical, laboratory and microbiological investigations, and followed longitudinally for 24 weeks. Reactive arthritis was diagnosed in 46 patients (19 induced by Chlamydia trachomatis, 27 by enterobacteria), 62 had undifferentiated arthritis, eight other inflammatory arthritic diseases, 15 acute sarcoid arthritis and 15 non-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…Whether primary or secondary to an obvious underlying cause, EN has been reported to be often associated with acute arthritis/periarthritis of ankle or with acute polyarthritis predominantly involving the lower segment of the body [4,8]. Although several authors have mentioned this as being mainly or exclusively a presentation of acute arthritis associated with sarcoidosis (often called Lofgren syndrome) [9,10,19], this was not the experience in the present study. Lofgren syndrome was found only in 2 patients.…”
Section: Discussionmentioning
confidence: 60%
“…Whether primary or secondary to an obvious underlying cause, EN has been reported to be often associated with acute arthritis/periarthritis of ankle or with acute polyarthritis predominantly involving the lower segment of the body [4,8]. Although several authors have mentioned this as being mainly or exclusively a presentation of acute arthritis associated with sarcoidosis (often called Lofgren syndrome) [9,10,19], this was not the experience in the present study. Lofgren syndrome was found only in 2 patients.…”
Section: Discussionmentioning
confidence: 60%
“…The diagnostic criteria for ReA shown in Table 6 were used in a recent study by Fendler et al (50) and resemble those used in other studies (71,107,113). It has been reported that elevated Creactive protein levels, genitourinary symptoms, metatarsophalangeal joint involvement, and HLA-B27 could predict the diagnosis of ReA with a sensitivity of 69.2% and a specificity of 93.5% (106).…”
Section: Diagnosismentioning
confidence: 99%
“…The second study 16 investigated 146 patients with UA with the outcome measure defined as SpA after 24 weeks, based on CRP > 20 mg/l, HLA-B27 positivity, metatarsophalangeal involvement, and presence of genitourinary symptoms. Additional followup was established after 1 and 2 years.…”
Section: Undifferentiated Arthritis Cohortsmentioning
confidence: 99%